Questions kids ask about this and that - Comely, Richard; Dickie, Alison (Grolier] [Toronto, 1989)
Questions Kids Ask About This and That provides simple, clear answers to a wide range of everyday questions children have about the world around them, sparking curiosity and encouraging learning.